The surgical outcome of primary trabeculectomy with mitomycin C and A fornix-based conjunctival flap technique in Thailand - Li Anne Lim (2018)
Objective: To determine the surgical outcome of primary trabeculectomy with mitomycin C (MMC) and fornix-based conjunctival flap technique in Thai patients. Material and Method: This retrospective review was conducted from the clinical records of all Thai glaucoma patients who underwent a primary trabeculectomy with MMC using a fornix-based conjunctival flap technique by or under supervision of one ophthalmologist (NK) between February 2004 and July 2006 at Siriraj Hospital, School of Medicine, Mahidol University, Bangkok, Thailand. Results: There were 69 eyes from 60 patients. Postoperatively, mean intraocular pressure (IOP) was significantly decreased from 26.1 ± 11.7 mmHg to 11.7 ± 4.4 mmHg (p < 0.001) and mean number of anti-glaucoma medication was significantly reduced from 3.9 ± 0.7 to 0.3 ± 0.9 (p < 0.001) at last visit. Sixty-seven eyes (96.8%) were considered as success. Eight eyes (11.6%) in this group needed topical anti-glaucoma medications. Two eyes (2.9%) were considered as failure. Mean follow-up period was 7.7 ± 4.0 months. Complications included bleb leaking in 16 eyes, choroidal detachment in four eyes, and blebitis in two eyes. Seven eyes with leaking bleb resolved spontaneously. Conclusion: Primary trabeculectomy with MMC using a fornix-based conjunctival flap technique is effective as a treatment for Thai glaucoma patients. There is a high rate of success (96.8%) with the low rate of complication.